RELEVANSI DAN RELIABILITAS GOODWILL (Sesudah Penerapan ED PSAK 22 Revisi 2010) - Theresia Hesti Bwarleling (Jurnal Akuntansi Bisnis, 2017)
The purpose of this study is to examine the value relevance and reliability of reported goodwill under PSAK in 2011; a period characterised by accounting treatment for goodwill which was showing the value relevance and reliability of reported goodwill after the adoption of IFRS  (ED PSAK 22 revision 2010). By using an adaptation of Feltham and Ohlson (1995), this study found that for the average Indonesian company the information presented with respect to goodwill is value relevant but not reliable. In particular, goodwill tends to be reported conservatively Keyword : relevance, reliability, goodwill, ED PSAK 22 revision 2010